The harvestmen fauna (Arachnida: Opiliones) from the Sub Mediterranean region of Slovenia - II - Novak, Tone (Annales. Series historia naturalis, 2005)
In the present paper, further findings of harvestmen in the Sub Mediterranean region of Slovenia are presented, and comments on some actual problems with the species are added. With the exception of the possible discovery of a troglobitic species in the region, all species living there have presumptively been recorded. With the exclusion of Trogulus gr. nepaeformis and T. gr. tricarinatus, where more species are expected, 34 species and one subspecies have been found in the region. About 20 opilionid species are typical of the region; the others occur in the marginal habitats bordering other zoogeographical regions.
Keywords: Arachnida; biogeografija; biogeography; Opiliones; pajkovci; Slovenia; Slovenija; submediteran; suhe južine; zoologija; zoology